Implementasi Pendidikan Multikultural dalam Mencegah Ekstrimisme Anak di RA Mubarokah - Khairunnisa Ulfadhilah; Pudin Saripudin; Salsabila Dwi Nurkhafifah (Institut Agama Kristen Negeri Manado, 2025)
Multicultural education at RA Mubarokah is implemented as a strategy to prevent extremismamong children. Through a qualitative narrative approach, this study explores the practicalexperiences of teachers and students in an inclusive learning environment. In this context,multicultural education not only serves as an introduction to various cultures, but also as aforum to build tolerance, empathy, and intercultural understanding. Activities such as groupdiscussions, art performances, and celebrations of religious holidays are designed to showcase cultural diversity and eliminate stereotypes that can fuel extremist attitudes. Teachers play a key role in educating children about the importance of mutual respect for differences, which is a foothold in building a positive personality. Through interviews and direct observation, it was found that children began to show behavioral changes that led them to an attitude of mutual respect. The study also highlights the challenges faced in the implementation process, such as resistance from the surrounding environment and lack of resources. However, the results show that a consistently applied multicultural education can contribute significantly to creating a safe and peaceful environment, thus forming a younger generation that understands and appreciates differences. Through this understanding, it is hoped that children can grow into individuals who not only prevent extremism, but also become agents of positive social change in society. This study emphasizes the importance of integrating multicultural values in the early childhood education curriculum as a preventive measure against the potential for extremism in the future